Numerical Investigation of Stall Characteristics of Common Research Model Configuration Based on Zonal Detached Eddy Simulation Method - Xin Zhang; Heng Zhang; Jie Li (Aerospace, 2023)
A zonal detached eddy simulation (ZDES) method, based on the two-equation k-ω SST turbulence model, was employed to predict stall characteristics and capture small-scale vortex structures in the wake region of the main wing under the post-stall condition of the Common Research Model (CRM) configuration. Additionally, the unsteady Reynolds-averaged Navier–Stokes (URANS) method was utilized for performance comparison in resolving small-scale vortices with ZDES. The results revealed a pronounced lateral flow on the wing, induced by the low-pressure region of the inner wing at post-stall angles of attack. Due to the downwash effect, the horizontal tail was influenced by the vortices in the wake region of the main wing, which the URANS method did not capture adequately. As the angle of attack increased, the separation area on the main wing expanded from the middle of the wing towards the inner wing. Consequently, the vortex structures in the wake region of the main wing became more intricate, and the primary peak of the lift coefficient spectrum shifted to the low-frequency region.